Communicative Approach to Determining the Role of Personality in Science - Kubalskyi, O. N. (Anthropological Measurements of Philosophical Research, 2022)
Purpose. This article aims at outlining the socio-communicative prerequisites for the influence of personality on the acquisition of rigorous scientific knowledge. Theoretical basis. The communicative foundations of an individual’s activity in general and the functioning of his consciousness in particular were laid by the philosophy of Edmund Husserl, primarily due to his introduction of the concepts of "intersubjectivity" and "lifeworld". From these positions, attempts were made to understand the discussion of Karl Popper and Thomas Kuhn regarding the role of the individual in science, in particular, the concept of a "normal scientist" as a participant in the lifeworld of scientists who support special intersubjective norms of reproduction of this lifeworld through scientific communication. The concept of "communicative mind", correlated with the philosophy of Jürgen Habermas, best expresses the rational and argumentative principles of achieving consensus in science. Originality. Social anthropology reveals the constitutive significance of teamwork in science as a way of achieving rigorous scientific knowledge. Social phenomenology concretizes this by emphasizing the need for constant improvement of the rules of this communication. The verification of scientific knowledge by facts is strictly determined by the observance of community-recognized scientific tools for achieving such verification, in particular, the conventional agreement within a certain community of scientists regarding the language of science, which is used to describe verification, falsification, and other procedures for organizing scientific knowledge into a system. Conclusions. Verification of the obtained scientific knowledge critically depends on the formulation, dissemination and observance of certain institutional rules of scientific communication. This applies, in particular, to the conventionally recognized rules for the verification of scientific knowledge by empirical facts: it is not an isolated scientist who should identify, verify, organize and evaluate empirical facts, but a community of scientists who conduct scientific research in an organized manner. Team scientific work is a special case of collective action, which is characterized by a high level of reflection and application of critical thinking on a communicative basis. In particular, the legitimation of acquired scientific knowledge occurs in the process of scientific research due to the observance of procedural rules and careful work with empirical facts.